2021
DOI: 10.26444/jpccr/132014
|View full text |Cite
|
Sign up to set email alerts
|

Isobolographic<i> in vitro</i> interactions of fluconazole with citrus essential oils against <i>Cladosporium cladosporioides</i>

Abstract: Wróblewska-Łuczka P. Isobolographic in vitro interactions of fluconazole with citrus essential oils against Cladosporium cladosporioides. J Pre-Clin Clin Res.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 30 publications
0
2
0
2
Order By: Relevance
“…The isobolographic analysis of interactions between fluconazole and essential oils against Aspergillus fumigatus showed additive interactions for the combination of fluconazole with lemon, orange and grapefruit oils and an additive interaction with a tendency to synergism for the combination of fluconazole with tangerine oil. Other studies for Cladosporium cladosporioides showed additive interactions for the combination of fluconazole with orange and grapefruit essential oil and additive with a tendency for synergism for combination of fluconazole with lemon and tangerine essential oils [26]. Additive interactions between fluconazole and essential oils may be related to the fact that both fluconazole and essential oils inhibit the activity of cytochrome P450 (CYP) enzymes in fungi.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The isobolographic analysis of interactions between fluconazole and essential oils against Aspergillus fumigatus showed additive interactions for the combination of fluconazole with lemon, orange and grapefruit oils and an additive interaction with a tendency to synergism for the combination of fluconazole with tangerine oil. Other studies for Cladosporium cladosporioides showed additive interactions for the combination of fluconazole with orange and grapefruit essential oil and additive with a tendency for synergism for combination of fluconazole with lemon and tangerine essential oils [26]. Additive interactions between fluconazole and essential oils may be related to the fact that both fluconazole and essential oils inhibit the activity of cytochrome P450 (CYP) enzymes in fungi.…”
Section: Discussionmentioning
confidence: 99%
“…Isobographic analysis is mainly used to evaluate drug interactions in animal studies. In in vitro microbiological studies it has been used only several times, mainly to assess the interaction of fluconazole with citrus essential oils against Cladosporium cladosporioides [26], the interaction of antibiotics in the treatment of Aspergillus fumigatus [27][28][29][30], or the assessment of interactions between antibiotics in the treatment of mycobacterial infections Mycobacterium [31].…”
Section: Introduction and Objectivementioning
confidence: 99%
“…Analiza izobolograficzna jest metodą statystyczną, pozwalającą precyzyjnie ocenić farmakodynamiczne interakcje pomiędzy stosowanymi lekami czy substancjami chemicznymi. Głównie wykorzystywana jest w badaniach na zwierzętach, choć coraz częściej obserwuje się jej zastosowania w badaniach in vitro prowadzonych na komórkach nowotworowych [27,28] czy w badaniach mikrobiologicznych [16,[29][30][31]. Flukonazol jest wykorzystywany w niektórych badaniach eksperymentalnych jako standardowy lek o działaniu przeciwgrzybiczym względem m.in.…”
Section: Dyskusjaunclassified
“…Istotną kwestią obecnego doświadczenia jest ocena interakcji pomiędzy flukonazolem a olejkiem eterycznym pomarańczowym względem Aspergillus niger, która wykazała interakcję addytywną z tendencją do synergizmu. Interakcję addytywną połączenia tych związków wykazano względem Aspergillus fumiagatus [16] oraz Cladosporium cladosporioides [29]. Połączenie olejku eterycznego Citrus aurantium z flukonazolem oraz amfoterycyną B dawało interakcję synergistyczną w hamowaniu infekcji Candida albicans [49].…”
Section: Dyskusjaunclassified